Analisis Rasio Keuangan Terhadap Peran Perbankan Syariah Dalam Mengimplementasikan Keuangan Inklusif Di Indonesia: Studi Pustaka Pada Laporan Keuangan Bank Syariah Bukopin 2010-2014 - Ersi Sisdianto; Nova Carissa; Novita Sari; Oktaviona Wijayanti; Retno Mei Saputri; Yuliana Yuliana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the role of sharia banking in implementing financial inclusion in Indonesia. Financial inclusion is a process to provide formal financial access for poor and low-income people (unbankable people). This research uses a qualitative and quantitative approach (mixed research). Qualitative data analysis uses analysis techniques developed by Straruss and Corbin with three major steps, namely open coding, axial coding, and selective coding. Quantitative data analysis uses comparative analysis of financial reports in 2010-2014 and analysis of financial ratios in the form of CAR, ROA, ROE, NPF and FDR. This research proves that sharia banking has great potential in implementing financial inclusion, shown by significant growth in funding and financing in 2010-2014 and the results of financial ratio analysis also show that the performance and financial condition of sharia banking is good.